The Business Perspectives Strategy Towards the TKI (Indonesian Migrant Workers) Market - Sihombing, Haeryip; Yaakob, Mohd Yuhazri; Safarudin, Mochamad (2011)
The business prospects and opportunities of the migrant workers’ (TKI) market are still wide open. This is shown by year to year remittances incremental of TKI that corresponds to a beneficial opportunity of the business players to optimize their exploration of this market. In reality, the current efforts and strategy in this exploration, however, are still not utilized effectively in terms of competitive advantage. Therefore, the initiative strategy towards product differentiation and innovation of the offered service should be explored and optimized based on the sustainable beneficial prospects for the business. As described briefly in this paper through a case of business innovation towards differentiation, the proposed strategies such as localization and two-sided market are required for business organizations to unlock their product innovation strategy towards TKI (as their customer) through the innovative solution against the poverty.